Framing dalam Media Over the Top: Kajian Literatur terhadap Film Dokumenter Ice Cold: Murder, Coffee, and Jessica Wongso - Nurhaliza, Adinda Aulia; Sari, Rizka Annisa; Alinda, Yunati (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The Netflix documentary, "Ice Cold: Murder, Coffee, and Jessica Wongso," generated significant public interest and widespread social media discussion by offering a novel perspective on the 2016 trial, contrasting with conventional media narratives that had previously accused Jessica Wongso of culpability. As a subscription-based Over The Top (OTT) platform, Netflix effectively influenced public opinion and perception of Jessica Wongso and other characters in the documentary by establishing a new narrative framework through emotional visualization and dramatic storytelling. This investigation aims to examine how Netflix shapes new public opinion and influences the public's perception of Jessica Wongso and other characters. The methodology involved a literature review examining five prior studies on framing from Google Scholar and SINTA-accredited journals. The findings demonstrate Netflix's effectiveness in altering public perceptions. The documentary substantially altered the public's perception of Jessica, initially depicted as cold, portraying her instead as a vulnerable figure possibly denied justice. Edi Darmawan Salihin, the victim's father, was also framed as an arrogant and dominant antagonist through visuals and interviews, underscoring documentary media's influence on individual perceptions. Discussions emerged regarding the reframing's endurance and the impact of social media posts (both official and prosumer) on its success, given the public's critical media consumption. In summary, "Ice Cold" effectively reframed the case narrative and influenced new public opinion, igniting widespread conversation.  Future research is advised to incorporate the victim's family's perspective and the evolution of public opinion following Jessica Wongso's parole for a more thorough and impartial study.